Substrates effect on Mesenchymal Stem Cells (MSCs) secretome and cellular subproteome - Geraldo, Ângela Margarida Ferreiro (2015)
Mesenchymal stem cells (MSCs) are adult multipotent cells that possess self-renewal capacity, have a high proliferative ability and are able to differentiate into mesodermal cell types. MSCs can be isolated from mesenchymal and extraembryonic tissues such as the umbilical cord matrix. The latter constitutes an attractive and alternative source of MSCs since these cells seem to be more naïve and possess higher proliferation capacity. In vivo, MSCs reside in a specialized microenvironment that is essential for the regulation of signaling, proliferation, migration and differentiation. Through mechanotransduction, mechanical forces of microenvironment are transduced into biochemical responses, which can lead to alterations in phenotype and lineage-specific differentiation, and changes in protein synthesis of MSCs. Based on these observations, this study aimed at exploring the effect of physical and biochemical substrate composition on the secretome and cellular subproteomes of MSCs derived from umbilical cord matrix. The present study revealed the modulation of the secretome and cellular subproteome profiles (soluble and membrane fractions) of MSCs cultured on soft substrates, with several proteins being modulated, namely the up-regulation of antioxidant proteins. Hence, we propose that MSCs cultured on soft substrates may constitute a population of cells with increased antioxidant properties, in principle allowing the cells to cope better with the stressful and hostile environments that they may encounter in vivo in a transplantation context.